Hirschsprung associated GDNF mutations do not prevent RET activation - Borghini, Silvia; Bocciardi, Renata; Bonardi, Giulia; Matera, Ivana; Santamaria, Giuseppe; Ravazzolo, Roberto; Ceccherini, Isabella (European journal of human genetics : EJHG, 2002)
Hirschsprung disease (HSCR) is a complex disorder characterised by aganglia of distal gastrointestinal tracts. The highest proportion of both familial and sporadic cases is due to mutations of the RET proto-oncogene. Five germline mutations in the glial cell-line-derived neurotrophic factor (GDNF) gene, one of the RET ligands, have been detected in HSCR patients. Pedigrees analysis and the observed association between these GDNF alterations and RET variants in the same patients raised the question of whether the GDNF gene plays any causative/predisposing role in HSCR pathogenesis. In the present work, we have studied the ability of GDNF proteins, each bearing one of the reported mutations, to activate RET by performing a functional test in cultured neuroblastoma cells. Consistently with the lack of genotype/phenotype correlation in human subjects, our results indicate absence of detectable alterations of mutant GDNF induced RET activation.